2007
DOI: 10.2337/db06-0436
|View full text |Cite
|
Sign up to set email alerts
|

IGF-Binding Protein-2 Protects Against the Development of Obesity and Insulin Resistance

Abstract: Proliferation of adipocyte precursors and their differentiation into mature adipocytes contributes to the development of obesity in mammals. IGF-I is a potent mitogen and important stimulus for adipocyte differentiation. The biological actions of IGFs are closely regulated by a family of IGF-binding proteins (IGFBPs), which exert predominantly inhibitory effects. IGFBP-2 is the principal binding protein secreted by differentiating white preadipocytes, suggesting a potential role in the development of obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
214
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(237 citation statements)
references
References 44 publications
12
214
3
2
Order By: Relevance
“…We now extend these observations and show that IGFBP1 predicts incident HF, all‐cause mortality, and CVD mortality in our cohort, along with 3 other regulators of metabolic disease and adipocyte function: IGFBP2, adipsin, and leptin. IGFBP2 is the predominant insulin‐like growth factor binding protein (IGFBP) produced by white adipose tissue and is thought to protect against obesity and insulin resistance in mice 8, 22. Previous studies, however, did not demonstrate any relation to CVD outcomes 10, 21.…”
Section: Discussionmentioning
confidence: 99%
“…We now extend these observations and show that IGFBP1 predicts incident HF, all‐cause mortality, and CVD mortality in our cohort, along with 3 other regulators of metabolic disease and adipocyte function: IGFBP2, adipsin, and leptin. IGFBP2 is the predominant insulin‐like growth factor binding protein (IGFBP) produced by white adipose tissue and is thought to protect against obesity and insulin resistance in mice 8, 22. Previous studies, however, did not demonstrate any relation to CVD outcomes 10, 21.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high IGFBP-2 levels as seen by overexpression of IGFBP-2 in mice appears to prevent diet induced obesity and insulin resistance, with IGFBP-2 also preventing murine adipocytes differentiation in vitro (Wheatcroft et al 2007b). Interestingly, recent studies by Xi et al (2013) have shown that IGFBP-2-based peptides containing the HBD motifs, efficiently inhibited preadipocyte differentiation in male mice, suggesting that IGFBP-2 cell surface interactions via these motifs might be implicated in the modulation of adipogenesis.…”
Section: Igfbp-2 and Metabolismmentioning
confidence: 99%
“…Consequently, it is necessary to assume that there are age‐ and tissue‐dependent effects of the RGD‐domain present in IGFBP‐2 for the control of fat accretion. At younger ages, overexpression of mouse IGFBP‐2 increased gonadal fat mass (Rehfeldt et al ., 2010), whereas overexpression of human IGFBP‐2 in mice blocked the development of age‐related obesity later in life (Wheatcroft et al ., 2007). The latter cannot be observed in the model included in this study; instead, these results indicate differential effects of mouse IGFBP‐2 in perinephric and other fat tissues.…”
Section: Discussionmentioning
confidence: 99%